Nitrogen and photosynthetic pigments in Cattleya maxima protocorms under LED spectra - Rahmadhani, Destiara Wulan; Setiowati, Frida Kunti; Sulisetijono, Sulisetijono (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Cattleya maxima is a valuable ornamental orchid with limited seed availability, making in vitro culture important for mass propagation. This study aimed to optimize protocorm quality through modification of ½ MS supplemented with Plant Growth Regulators (NAA + BAP) and glutamine under blue (455–480 nm) and white light irradiation. Media were evaluated: ½ MS, ½ MS + PGRs, ½ MS + glutamine, and ½ MS + PGRs + glutamine. Total nitrogen was measured using the Kjeldahl method and analyzed using two-way ANOVA, while chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids were analyzed using MANOVA. Culture medium significantly affected total nitrogen and photosynthetic pigments. The highest total nitrogen was recorded in ½ MS + glutamine, likely reflecting nitrogen accumulation from glutamine rather than active assimilation. Chlorophyll a and b were highest in ½ MS and ½ MS + PGRs, with no significant difference, while total chlorophyll and carotenoids were highest in ½ MS + PGRs. Glutamine supplemented reduced pigment accumulation, growth, and protocorm quality, producing pale green to translucent white protocorms. In contrast, media without glutamine produced greener protocorms with better growth. Spectrum effects were evaluated descriptively, white light tended to support growth, while blue light enhanced green coloration.